If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -7 = 12 Reorder the terms: -7 + 7x = 12 Solving -7 + 7x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 7x = 12 + 7 Combine like terms: -7 + 7 = 0 0 + 7x = 12 + 7 7x = 12 + 7 Combine like terms: 12 + 7 = 19 7x = 19 Divide each side by '7'. x = 2.714285714 Simplifying x = 2.714285714
| 8(s+3)=74 | | 121x-88=11(11x-8) | | 1=-(x+3) | | 12x+3=-4 | | 7x+18x-8=5(5x+6) | | t(w)=2w+40 | | 4(x+1.81)=3x | | ay+3a+2y+6=0 | | 3x-11=35 | | 4x^2-68x-280=0 | | 4078/X=2,39 | | 0.8+0.133x=0.933 | | 3x-6/x^2-2x | | 4r+7=23 | | 7*7-7=12 | | 3x+10=3x-2 | | 10w=3+98w | | 47-8x=11+10x | | (y-2/3)^2=4/9 | | 1.2k+2.3=-05k+7.4 | | kx^2+(3k-4)x-5=0 | | 20+5x=5x(x-3) | | 18-3/4x=12 | | 5m-4=6+4-2m | | 0.333x+0.444x=0.777 | | 6x-3+5x-7=8x+3x+10 | | 7/4=4x/3x-6 | | 4-x/-1 | | 5x+-3=3x+1 | | 7/9=g | | 24-8x=11+5x | | 6n+2(n-3)=18 |